Effective communication strategies for Maybank subsidiaries towards organizational performance of financial institutional group department, Menara Maybank, Kuala Lumpur / Khairul Fikry Saadon - Saadon, Khairul Fikry (Faculty of Business and Management, 2018)
Disagreement often occurred between subsidiaries and headquarters that lead to disorganized system and tasks. Communication channels between subsidiaries and headquarters of institution is unclear and subsidiaries are getting disconnect each and every day. Thus, the purpose of this research is to study the contributions of effective communication strategies within international subsidiaries towards organizational performance of Financial Institutional Group, Menara Maybank, Kuala Lumpur. A survey of organizational performance was conducted at Financial Institutional Group, Menara Maybank, Kuala Lumpur to determine the influence of the underpinnings relationship between one-way communication, interactional communication and transactional communication towards organizational performance in Financial Institutional Group, Menara Maybank, Kuala Lumpur. 71 data were collected using convenience sampling method. Researcher has used the SPSS 20.0 software, “Statistical Process for Social Science” to analyze and interpret data from questionnaires. The findings show that only variable one-way communication is significant in influencing organizational performance, interactional communication and transactional communication are not significant in determining organizational performance. This research was meant to enhance the relationship between employees in different subsidiaries and the headquarters management so that common ground is a lot easier to achieve which could lead to a better performance of the institution. Therefore, Financial Institutional Group of Menara Maybank, Kuala Lumpur should consider these variables to improve its performance.